APPROACHES GOING TO DETERMINATION PERIODS OF THE HUMAN FACTOR OF NAVIGATORS DURING SUPERNUMERARY SITUATIONS - Nosov, P. S.; Ben, A. P.; Safonova, A. F.; Palamarchuk, I. V. (Radio Electronics, Computer Science, Control, 2019)
Context. The problem of identifying the manifestation of the human factor in the context of utility in maritime transport during emergency situations is considered. The aim of the study is to increase safety in maritime transport by identifying positive and negative human factors, as well as analyzing the behavioral reactions affecting the vessel’s passage parameters. Objective. The aim of the work is to determine the approaches and the construction of software tools to identify periods of manifestation of the human factor of the navigators during abnormal situations. Method. The study identified the types of manifestations of the human factor in the form of intuitive (illogical) behavior of the navigator. The dependence of intuitive behavior, as a reaction, on exceeding the detection threshold of perception of service information, is given. It was determined that the distribution of information load among members of the navigation watch will significantly reduce the detection threshold of the navigator at the time of making management decisions. It was established that the detection step is to determine the balance of information effects on the navigator and his individual polar reactions. The cycle of updating the navigator model is determined by analyzing his individual behavior model of previous intellectual activity. A formal description of the space of alternatives and reactions of the navigator in the form of polar groups at the moment of vessel management is proposed. Software has been developed that allows the analysis of the vessel’s passage trajectory for collision detection and the identification of periods of occurrence of the detection threshold of the navigator. Analysis of the trajectories made it possible to conclude that before the collision the navigator was in active/passive polar states of action, which directly proportional to the speed of the vessel, which confirms the main hypothesis of the study. As a mathematical tool for solving the problem of classifying individual reactions of the navigator, the factor analysis and a training sample are offered – more than nine typical situations, which make it possible to adequately determine polar reactions according to the principle of utility. Results. In order to confirm the adequacy of the proposed formal-logical approaches, an experiment was conducted using the Trainer Professional 5000 navigation simulator (NTPRO 5000). The results of the experiment, as well as the developed software, made it possible to identify the time periods of the negative human factor manifestation of the navigator caused by the information overload and to determine its individual stimulus factors. At the same time, the moment of occurrence of an extraordinary situation was determined by analyzing the passage trajectory of the vessel by means of processing log files by passing the Bosporus strait location. In addition, an algorithm was developed for the formation of the navigator’s model and its updating on the basis of individual periods of the negative manifestation of the human factor. The features of the occurrence of informational imbalance between members of the navigation watch in the event of an emergency situation and features of its identification during the passage of the vessel are considered. The obtained results will allow at a qualitatively new level to approach the analysis of the problem of the influence of human factor on the adequate managerial decisions of the navigator. Conclusions. The proposed formal approaches and the developed software will allow identifying the transition from the controlled adequate state of the navigator to the uncontrolled state with intuitive reactions. The scientific novelty consists in the fact that the developed algorithm of forming a navigator model in a discrete time, which allows to identify its polar reactions during extraordinary situations. The practical significance lies in the fact that the results of the experiment allowed identifying the time periods of the manifestation of the negative human factor of the navigator, caused by the information overload and identifying its individual factors-incentives. Prospects for further research may be the development of software in the form of an expert system defining deviations from a given course during the sea passage, as well as inadequate reactions in the performance of classical maneuvers in case of divergence of ships in constrained areas.